The Bulbocavernosus Reflex in the Differential Diagnosis of Multiple System Atrophy with Predominant Parkinsonism and Parkinson’s Disease - Huang, Huan-jie; Zhu, Xing-yu; Wang, Xun; Wang, Zhang-yang; Zhang, Wan-li; Chen, Bi-cheng; Liu, Chun-feng (Frontiers in Neurology, 2018)
Multiple system atrophy with predominant parkinsonism (MSA-P) is a degenerative disorder that presents with autonomic dysfunction, atypical parkinsonism, and ataxia. Parkinson’s disease (PD) is an age-related neurological disorder of the central nervous system. Differentiation between MSA-P and PD is important because treatments, complications, and prognoses differ. The bulbocavernosus reflex (BCR) tests the afferent and efferent signals of the pudendal nerve as well as the sacral cord. In this study, we investigated differences in BCR parameters between MSA-P and PD patients. Thirty-eight MSA-P patients and 32 PD patients were selected to participate in our electrophysiological investigations. The Keypoint EMG/EP system was used to induce the BCR, and latencies and amplitudes were recorded for systematic statistical analyses. Area under the curve (AUC) of the receiver operating characteristic (ROC) was used to assess the specificity and sensitivity of the BCR parameters. A BCR was elicited in 76.32% of MSA-P patients and 93.75% of PD patients. The BCR latencies of the MSA-P group were longer than those of the PD group (p < 0.001). In addition, the MSA-P group had a lower BCR amplitude compared to the PD and control groups (p < 0.001). We discovered the difference between MSA-P and PD through BCR latencies and amplitudes. Compared to PD patients, MSA-P patients have longer latencies and lower amplitudes. Therefore, the BCR may be used to discriminate between MSA-P and PD in some cases.